ANALISIS BAHAYA DENGAN MENGGUNAKAN JOB SAFETY ANALYSIS PADA PEKERJAAN PENGELASAN PT SARANA BERKAT SESAMI DI BALIKPAPAN - rizal, muhammad (IDENTIFIKASI, 2020)
PT Sarana Berkat Sesami is a company engaged in fabrication, where its main activity is welding. Welding is the connection between two or more metals by utilizing heat energy. For this reason, it is necessary to handle potential hazards, so as to reduce the impact of work accidents and losses. The purpose of this study was to analyze the potential hazards at each sequence of welding work steps and determine the proper and appropriate control measures. This research was conducted with a qualitative approach, using Job Safety Analysis instruments to identify potential hazards and control them. The results of this study obtained potential hazards originating from humans, materials, machines, methods, and the work environment. These potential hazards include welding sparks and fires, UV and infrared radiation, welding dust and fumes, electric shocks, working position (ergonomics), incompetent conditions of workers. Controls are carried out based on a hierarchy of controls, namely engineering control, administrative control and personal protective equipment (PPE). In conclusion, from the reasoning work, there are 12 stages of work identified with potential hazards in all stages consisting of 39 potential hazards with the implementation of controls that include elimination, substitution, engineering control, administrative control and personal protective equipment to Indonesia.